IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI BERBASIS KEARIFAN LOKAL DALAM MENGGALI IDE-IDE KREATIF KEWIRAUSAHAAN DI SD NEGERI 1 NGRANTI - Nur Afwidah, Maria; Sujono, Imam; Setiani, Rahyu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the implementation of differentiated instruction based on local wisdom in fostering students' creative entrepreneurial ideas at SD Negeri 1 Ngranti. The research is motivated by the challenge of addressing diverse learning needs in the era of the Merdeka Curriculum, as well as the importance of cultivating entrepreneurial spirit through the utilization of local potential. The study aims to describe the planning, implementation, and evaluation of such instruction. A qualitative case study design was employed, involving fifth-grade teachers and students as research subjects. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles & Huberman interactive model. The results indicate that planning was conducted in an innovative and adaptive manner through diagnostic assessment and the development of differentiated teaching modules integrating local wisdom. The implementation was dynamic and contextual, utilizing content, process, and product differentiation, local-based concrete media, and interactive guidance. The evaluation was holistic, encompassing both process and outcome assessments, accompanied by feedback and continuous reflection. In conclusion, this instructional approach provided relevant and personalized learning experiences, effectively enhancing students’ creativity, independence, and entrepreneurial mindset while simultaneously preserving the local potential of Ngranti Village in alignment with the Merdeka Curriculum.